2020
DOI: 10.1111/cge.13759
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of specific exons of FHOD3 detected by next‐generation sequencing are associated with hypertrophic cardiomyopathy

Abstract: Despite new strategies, such as evaluating deep intronic variants and new genes in whole‐genome‐sequencing studies, the diagnostic yield of genetic testing in hypertrophic cardiomyopathy (HCM) is still around 50%. FHOD3 has emerged as a novel disease‐causing gene for this phenotype, but the relevance and clinical implication of copy‐number variations (CNVs) have not been determined. In this study, CNVs were evaluated using a comparative depth‐of‐coverage strategy by next‐generation sequencing (NGS) in 5493 HCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…A partial disconnect is often observed between particular genetic variants and phenotypic presentation in cardiomyopathies, and it has been suggested that this may be due to factors such as modifier genes, epigenetics, environment, or incomplete penetrance [72]. Thus, mutations of the fhod-1-related human gene, FHOD3, have been suggested to cause HCM, but there is imperfect correspondence between a given FHOD3 mutation and the development of disease [6,[9][10][11]. Our findings point to the possibility that one contribution to variability may be interplay between FHOD3 and perturbations in the ubiquitin proteasome system (UPS), a known contributor to cardiomyopathy [73].…”
Section: Formin Activity Is Important For Normal Proteostasis Of Myosin In Worm Bwmmentioning
confidence: 99%
See 2 more Smart Citations
“…A partial disconnect is often observed between particular genetic variants and phenotypic presentation in cardiomyopathies, and it has been suggested that this may be due to factors such as modifier genes, epigenetics, environment, or incomplete penetrance [72]. Thus, mutations of the fhod-1-related human gene, FHOD3, have been suggested to cause HCM, but there is imperfect correspondence between a given FHOD3 mutation and the development of disease [6,[9][10][11]. Our findings point to the possibility that one contribution to variability may be interplay between FHOD3 and perturbations in the ubiquitin proteasome system (UPS), a known contributor to cardiomyopathy [73].…”
Section: Formin Activity Is Important For Normal Proteostasis Of Myosin In Worm Bwmmentioning
confidence: 99%
“…Another sarcomeric component of cardiac muscle is formin homology 2 domain containing 3 (FHOD3) [3,4], a member of the formin family of proteins. Mutations in the FHOD3 gene have recently been shown to be a genetic cause of HCM, while other mutations have been associated with DCM [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another sarcomeric component of cardiac muscle is formin homology 2 domain containing 3 (FHOD3) [3,4], a member of the formin family of proteins. Mutations in the FHOD3 gene have recently been shown to be a genetic cause of HCM, while other mutations have been associated with DCM [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In mice, knock out of the FHOD3 gene leads to death from heart failure by embryonic day 11.5 with appearance of immature sarcomere-containing premyofibrils/stress fiber-like structures with immature Z-lines that fail to mature into myofibrils [21]. In contrast to the full knockout or knockdowns of FHOD3 in mouse or cultured cell studies, most identified human variants of FHOD3 related to HCM or DCM are missense mutations [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%